Robô-INOVEE: Robotic Platform with Programming Assisted by Artificial Intelligence - Mesquita, Leonardo [UNESP]; de Lucena, Samuel Euzédice [UNESP]; de Sena, Galeno José [UNESP]; Akamatsu, Jânio Itiro [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2025)
This article presents the robotic platform Robô-INOVEE, developed by the Center for Innovation in Energy Efficiency (INOVEE), aiming to support the teaching of robotics and programming logic at different levels of education, from basic education to higher education. Robô-INOVEE can be programmed with the help of free software tools, such as Autodesk Tinkercad ${ }^{\text{TM }}$, using coding or visual programming languages, and also supports artificial intelligence (AI)-assisted programming, for example, with the use of Gemini or ChatGPT tools. Based on the Arduino Nano board, Robô-INOVEE offers a robust and versatile architecture equipped with several sensors, actuators and communication modules, allowing its programming for various applications. Integration with AI expands the possibilities for experimentation, making Robô-INOVEE a rich tool for the development of computational thinking, interdisciplinarity and skills formation.